Green Financing: Peran Pembiayaan Berbasis Syariah dalam Transisi Energi Berkelanjutan di Indonesia - Devina Firda Rahman; MH Ainulyaqin; Kisanda Midisen; Sakum; Yudianto Achmad (Jurnal Ilmiah Ekonomi Islam, 2026)
The sustainable energy transition has become a strategic agenda for Indonesia to achieve its New and Renewable Energy (NRE) mix target and net-zero emissions by 2060. However, renewable energy development still faces challenges, particularly the limited availability of long-term financing. This study aims to analyze the development of green financing in Islamic banking, its role in supporting the sustainable energy transition, and the challenges of its implementation. This research employs a qualitative method with a library research design. Data were collected from annual reports and sustainability reports of Islamic banks, publications of the Financial Services Authority (OJK) and the Ministry of Energy and Mineral Resources (ESDM), as well as relevant scientific journals. The findings indicate that green financing in Islamic banking showed positive development during 2022–2024, with total financing amounting to IDR 75,137.855 billion in 2022, IDR 66,585.894 billion in 2023, and IDR 73,845.327 billion in 2024. The financing was primarily directed toward renewable energy, energy efficiency, and environmentally friendly projects. However, its implementation still faces challenges related to regulations, sustainable finance literacy, and financing risks. This study concludes that Sharia-based green financing has significant potential to support the acceleration of Indonesia’s sustainable energy transition.